Kajian Komparasi Ukuran Utama Kapal Penumpang Catamaran Antara Bahan FRP Dan Aluminium - Hardjono, Soegeng (Warta Penelitian Perhubungan, 2012)
ABSTRACTIn general, design of Cata111ara11 passe11ger boats have been mostly made of FRP or aluminum materials. Tl1e sclectio11 of FRP or Aluminum material has an influence on the value of the lioats main di111msio11s, especially relating to the draft, speed, power, passenger capacity and displacement. HaPi11g m1alyzcd tile 111ain dimensions of both FRP and aluminum boats for the same passenger capaci~/ by using parametric ratio and regression analysis, It has been found that the majorihJ of boat main dimension values of FRP Catamaran is larger, among others,are 49 % for the lengtll (L), 0.34% for the breadth (B), 47% for the high (D), 62% for the speed (V), and 74% for tile engine power (HP). However, the other dimensions of FRP Catamaran namely the draft (T) and the displacement are 0.86% and 34%smaller respectively. For thesame value of length for both types of boats, the result of statistical analysis stated that most of tile major dimension of Aluminiun1 Catamaran boats appears to be larger, among others, are about 48% for tile breadth  B), 1 % for the high (D), 50% for the draft (f), 130% for th Displacement (weight of the ship), 20% for HP (engine power) and 48% for passenger capacity. Hmvever, speed (V) and engine power (HP) of FRP Catamaran boats are 33% and 20% higher respectively.Key Words:. Comparison, main dimensions, passenger Catamaran, FRP, Aluminum